The learning environment as a space for changes - Jolanta Nowak (Problemy Wczesnej Edukacji)
Science is not a simple increase of knowledge, but a change in state of mind. This demands a personalized approach to the teaching/learning process, the consideration of new spaces serving to gain information and experiences, as well as making use of the dialogical nature of man to create a learning community. The child cannot be a background for teachers’ actions but an authentic real creator of his/her development. School should evolve from a socially and culturally authorised knowledge-transferring institution into an agency which will be a community of life and work. This paper focuses on selected aspects of a new culture of learning: constructive, self-regulated, situated and collaborative, that prepares the student for smooth functioning in a world marked by change.